Situating H.D. Thoreau's _Walden_ within Post-Exceptionalist American Studies. Exceptionalism Reconsidered - Šesnić, Jelena (Array, 2013)
As a reaction to the latest revisionary trend within American studies challenging the notion of US exceptionalism, the article looks at ways of reading "hypercanonized" US texts, such as H.D. Thoreau's _Walden_, from the vantage point of world-systems theory and comparative literature methodology. It is argued that new methodologies complicate readings of classic US texts and align them with other "planetary" or global literary phenomena.